Ethical responsibility of journal editors and authors when publishing scientific publications / Etična odgovornost pri objavljanju znanstvene publikacije urednikov revij in avtorjev - Pahor, Dušica (Acta Medico-Biotechnica, 2021)
Ethics has been and always will be an important part of scientific research. Guidelines are not always followed, however, and we must, on the basis of experience, take care to ensure that science remains ethical. Indeed, ethics is a consideration that pertains to all areas of research. Unethical practices in the pursuit of success, fame, or personal benefit must be strictly controlled to prevent the possibility of misusing science. This is the wish and the mission of our editorship.